Comparison of training and competition opportunities in leisure time among people with intellectual disabilities in selected European countries - Lucie Francova; Hana Valkova; Roman Sinkovsky (Montenegrin Sports Academy, 2013)
Leisure time activities are important for individuals with an intellectual disability (ID) Table tennis (TT) seems to be the most suitable and accessible activity in relation to motor skills and low financial requirements. The aim of the project was to investigate the opportunities for the TT training and competition among individuals with ID in the following European countries: Austria, the Czech Republic, England, and Hungary. Those countries regularly participate in international TT events organized by Inas. The coaches of the mentioned countries were questioned about the TT training process of persons with ID during their leisure time. The survey was completed by 4 coaches (3 male and 1female), who work at various levels (from the lowest level in sports clubs to the top level in national teams) in each country. The research findings showed that all of the surveyed couches practiced trainings frequency two times per week. In addition to national games, all the countries organize competitions at regional levels and par¬ti¬ci¬pa¬te in international events. The data reveal that training camps lasting from 5 to 14 days per year are organized in all the sur¬veyed countries. The survey found certain training options, which correspond more to the standard of the recreational sport than to the standard of the top-level sport. A positive finding was the possibility of training with the intact population, which may be con¬si¬de¬red as an important phenomenon of social inclusion.